Lack of association between interleukin 6 gene promoter polymorphisms and aneurysmal subarachnoid hemorrhage in Turkish population [Türk toplumunda İnterlökin 6 gen promoter polimorfizmleri ve anevrizmal subaraknoid kanama arasındaki İlişki eksikliği] - (:unkn) unknown (Ege University Press, 2015)
Background: The IL6 gene is related to several disease states. Its relation to aneurysm formation and aneurysmal SAH has been studied in the literature, but the reported results have not resulted in definite positive or negative data. In this study we aimed to examine IL6 gene polymorphisms in a Turkish population and further our understanding of the relationship. Results: We included 120 intracranial aneurysm SAH cases and 120 healthy controls to examine whether there was a genotype difference between these groups in the -174 G > C and -572 G > C promoter polymorphisms located in the IL6 gene. The differences between groups were studied using a chi-squared test. There was no statistical difference between aneurysmal SAH patients and controls for IL6 promoter 174G > C and 572G > C polymorphisms. Conclusions: IL6 promoter SNPs did not show a correlation with intracranial aneurysm formation and subarachnoid aneurysmal rupture in a Turkish population, but genetic differences between ethnic populations may give different results. © 2015, Ege University Press. All rights reserved.
Keywords: Genotype; IL6 gene; Intracranial aneurysm; Polymorphism